Congenital Proximal Radioulnar Synostosis in an Elite Athlete–Case Report - Ilja Chandoga; Róbert Petrovič; Ivan Varga; Boris Šteňo; Emὄke Šteňová (Medicina, 2023)
Background and Objectives: Proximal radioulnar synostosis (PRUS) is the most frequent congenital forearm disorder, although the prevalence in the general population is rare with a few hundred cases reported. Pfeiffer, Poland, Holt–Oram, and other serious congenital syndromes contain this abnormality. Non-syndromic cases with isolated PRUS very often exhibit as SMAD6, NOG genes variants, or sex chromosome aneuploidy. A subgroup of patients with haematological abnormalities presents with HOXA11 or MECOM genes variants. Case report: We present a non-syndromic adult elite ice-hockey player with unilateral proximal radioulnar synostosis of the left forearm. In early childhood he was able to handle the hockey stick only as a right-handed player and the diagnosis was set later at the age of 8 years due to lack of supination. Cleary–Omer Type III PRUS was found on x-ray with radial head hypoplasia and mild osteophytic degenerative changes of humeroulnar joint. Since the condition had minimal impact on sports activities, surgical intervention was not considered. The player continued his ice-hockey career at the top level and joined a national team for top tournaments. Upper extremity function assessment with questionnaires and physical testing resulted in minimal impairment. The most compromised tool was the Failla score with 10 points from a total of 15. Genetic testing with Sanger sequencing revealed no significant pathogenic variant in SMAD6, NOG, and GDP5 genes. No potentially pathogenic copy number variants were detected by array-based comparative genomic hybridization. Conclusions: In the reported case, the ability of an athlete to deal with an anatomic variant limiting the forearm supination is demonstrated. Nowadays, a comprehensive approach to rule out more complex musculoskeletal impairment and family burden is made possible by evolving genetics.